Instant Gloss: Promoting Paint in 1840s Paris. The Example of Louis Viard’s Chromo-Duro-Phane Varnish - Spennemann, Dirk H.R. (Studia Historiae Oeconomicae, 2021)
To successfully promote his products, the small-scale paint manufacturer Louis Viard employed a range of strategies. These ranged from the true and tried media of newspaper advertisements, product packaging and advertising cards to more innovative modes of promotion, such as mobile advertising on delivery carts as well as flamboyant street processions, to clever and engaging use of billboards and product placement in plays. In addition, he maintained a workforce of loudly attired roaming painters, who combined promotion and marketing at the same time.